Functional Outcome of Proximal Fibular Osteotomy in Medial Compartment Osteoarthritis of The Knee Joint (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: Proximal Fibular Osteotomy (PFO) has been proposed as a new surgical option for pain relief in patients with medial compartment knee osteoarthritis. It is simple, safe and affordable. To assess functional outcome of proximal fibular osteotomy in medial compartment osteoarthritis of knee joint.Materials and methods: This prospective hospital based clinical trial was carried out in the Department of Orthopedic Surgery Chittagong Medical College Hospital (CMCH) Chattogram from July 2019 to June 2020. A total of 30 patients with knee osteoarthritis were enrolled through inclusion and exclusion criteria by purposive sampling. Proximal fibular osteotomy was done after taking written informed consent. Data was recorded in a predesigned case record form. All the patients were followed up to 6 months when final outcome was assessed by Oxford Knee Score. All the data were analyzed statistically by using Statistical Package for Social Sciences (SPSS-25). The result was expressed as frequency, percentage and mean ± SD. Level of significance was calculated at p